Seasonal variation in the brain μ-opioid receptor availability - Sun Lihua; Tang Jing; Liljenbäck Heidi; Honkaniemi Aake; Virta Jenni; Isojärvi Janne; Karjalainen Tomi; Kantonen Tatu; Nuutila Pirjo; Hietala Jarmo; Kaasinen Valtteri; Kalliokoski Kari; et al. (United States, 2022)
Seasonal rhythms influence emotion and sociability. The brain μ-opioid receptor (MOR) system modulates a multitude of seasonally varying socioemotional functions, but its seasonal variation remains elusive with no previously reported in vivo evidence. Here, we first conducted a cross-sectional study with previously acquired human [11C]carfentanil PET imaging data (132 male and 72 female healthy subjects) to test whether there was seasonal difference in MOR availability. We then investigated experimentally whether seasonal variation in daylength causally influences brain MOR availability in rats. Rats (six male and three female rats) underwent daylength cycle simulating seasonal changes; control animals (two male and one female rats) were kept under constant daylength. Animals were scanned repeatedly with [11C]carfentanil PET imaging. Seasonally varying daylength had an inverted U-shaped functional relationship with brain MOR availability in humans. Brain regions sensitive to daylength spanned the socio-emotional brain circuits, where MOR availability formed a spring-like peak. In rats, MOR availabilities in the brain neocortex, thalamus and striatum peaked at intermediate daylength. Varying daylength also affected the weight gain and stress hormone. We conclude that the in vivo brain MOR availability in humans and rats shows significant seasonal variation, which is predominately associated with seasonal photoperiodic variation. Given the intimate links between MOR signaling and socioemotional behavior, these results suggest that the MOR system might underlie seasonal variation in human mood and social behavior.